Preparation and Morphological Study of Epoxy/Silane Modified Nanoclay Nanocomposites - KHOEINI*, M.; BAZGIR†, S.; TAMIZIFAR‡, M.; NEMATI§, A.; ARZANI¶, K. (Asian Journal of Chemistry, 2009)
Epoxy-clay nanocomposites were prepared using silane modified montmorillonite. The clay was first purified using a 1-inch hydrocyclon apparatus. The purified clay was modified with various amounts of (γ)- 3-aminopropyltrimethoxysilane as a modifier. The synthesized organoclay was mixed and swollen by a mixture of epoxy resin and stoichiometric amount of curing agent at different temperature, mixing time and agitation. Finally, the compounds were cured in an oven at 90 ºC for 2 h. The nanostructure materials were characterized using X-ray diffraction and transmission electron microscopy. The X-ray diffraction patterns showed that the impurities and large particles (greater than 5 microns) are removed from the samples. The results showed that interlayer spacing was increased with increasing the amount of modifier and the basal distance in the organoclay was more than 2.1 nm which was larger than that of the original clay (1.24 nm). The X-ray diffraction patterns showed that the interlayer spacing of clay in the nanocomposite was increased and the 001 peak of the Montmorillonite was shifted to smaller 2 theta and in many cases disappeared. The X-ray diffraction and transmission electron microscopy results demonstrated that the layers of clay in the nanocomposite samples were fully exfoliated.